Biological Investigation of Aqueous Extract of Funnel Seeds to Check its Therapeutic Effects in the Management of Polycystic Ovarian Syndrome in Induced PCOS Female Albino Rats - Naseer, Maha; Asad, Ayesha; Akram, Sajeela; Aslam, Kiran; Irfan, Azka Momina; Niaz, Fizza; Qura-tul-ain (Indus Journal of Bioscience Research, 2024)
About every one out of nine women around the globe is living with polycystic ovarian syndrome. Polycystic ovarian syndrome is characterized by increased male hormone (androgen) in female body that results in delayed ovulation by unbalancing follicle stimulating hormone, luteinizing hormone, testosterone, and insulin levels. Other associated signs are increased insulin levels due to elevated androgens, weight gain, male pattern hair growth, and depression. Funnel seed is a wonder in regulating the imbalanced reproductive hormones. The purpose of Current study was to evaluate the hormone regulating properties by using funnel seed as source element. For this purpose, 14 female albino rats with induced polycystic ovarian syndrome were divided into two group. Treatment group was given funnel seed extract in dose of 50mg/kg of the body weight for sixty days. Levels of follicle stimulating hormone, luteinizing hormone, testosterone and insulin levels were measured and compared in blood samples on 0th day and 60th day in study groups. Insulin and testosterone levels were significantly (p<0.05) lower in the treatment group, whereas ovulating hormones, such as follicle stimulating hormone and luteinizing hormone, were significantly (p<0.05) higher.